BAD HABITS AS A FACTOR DESTROYING HUMAN HEALTH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, harmful habits and the changes caused by their influence on the human body, as well as their prevention, are disclosed.